Level of situational motor abilities qualitative changes and football player`s performance successfulness under the influence of complex football training - Jeleskovic, E.; Talovic, M.; Alic, H.; Bajramovic, I. (Homosporticus, 2008)
The aim of the research is to determine the level of qualitative changes of situational motor abilities of situational motor abilities and performance successfulness of football players under the influence of the complex football training. The samples of examinees represent 107 football players, 16 to 17 years old. All of the examinees are registered football players in cadet teams` competing in municipality and regional leagues. They are involved in long-term training process in their clubs and taking that in consideration they are the bearers of football quality in this age group. Variables selected for this examination hypothetically covered the area of specific motor abilities with 11 variables and are of performance successfulness in football with 15 variables, 7 variables for the successfulness in defense and 8 for forward successfulness. The programming of training activities applied in this investigation had multidimensional character, whereas through the different training methods we tried to improve the situational motor abilities as well as the performance successfulness in football game. Load quantity was according to the age characteristics of the sample, and was applied through the 134 training matches and 46 matches (28 leagues and 18 controls). For the determination of the quality changes created under the influence of complex football program, notable in a change of situational motor abilities ang performance succesfullness in football game, we aplied the factor analysis - congruency metod. General analysis of the program with its operators, methods and load had significant influence at qualitative changes in situational motor abilities, and in area of performance successfulness in football game we can say that the structure had no rearranging of the variables in isolated factors. Therefore we can conclude that there were no statistically significant qualitative changes. Based on the results we can conclude that the treated sample reached high level of specific, technical training, which now should be applied more in a match and get to know all the unpredicted situations when confronted with the opposite team player.